2020
DOI: 10.1177/0896860820953050
|View full text |Cite
|
Sign up to set email alerts
|

Successfully treating three patients with acute kidney injury secondary to COVID-19 by peritoneal dialysis: Case report and literature review

Abstract: Coronavirus Disease 2019 (COVID-19) is a pandemic disease that increased the burden on health-care system. In the Kingdom of Saudi Arabia, 74,795 cases have been reported until 26 May 2020 and the number of cases is rapidly increasing. The mortality rate of COVID-19 worldwide is 6.37%. Here we report three cases of acute kidney injury (AKI) secondary to pneumonia of severe COVID-19; they were treated with automated peritoneal dialysis (PD) with full recovery. To the best of our knowledge, few reports in the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 5 publications
1
9
0
Order By: Relevance
“…All forms of RRTs have been employed. Peritoneal dialysis has been tried successfully and remains a valuable tool especially during periods of acute surge in the number of patients requiring RRT [ 26 , 27 ]. The modality of RRT is often selected based on patient characteristics and resource availability.…”
Section: Discussionmentioning
confidence: 99%
“…All forms of RRTs have been employed. Peritoneal dialysis has been tried successfully and remains a valuable tool especially during periods of acute surge in the number of patients requiring RRT [ 26 , 27 ]. The modality of RRT is often selected based on patient characteristics and resource availability.…”
Section: Discussionmentioning
confidence: 99%
“…Since heart failure dramatically worsens and requires urgent care, it is important to confirm heart failure associated with COVID-19 and begin individualized treatment, including diuretics or dialysis [ 7 ]. Although several cases of urgent peritoneal dialysis for acute kidney injury and heart failure induced by COVID-19 have been reported, there have been only a few case reports of heart failure caused by COVID-19 in maintenance PD patients to date [ 8 , 9 ]. Jiang et al recently reported an observational study in PD patients during the COVID-19 outbreak.…”
Section: Discussionmentioning
confidence: 99%
“…Coronavirus Disease 2019 (COVID-19) has widely spread in the worldwide scale with serious disaster [1].Acute kidney injury (AKI) has a higher rate of morbidity and mortality in common complication for critical illnesses and counted about 5-7 % of hospitalized patients in world [2].-Several studies have evaluated the development of AKI is more strongly related to worse outcomes and mortality rates of COVID-19, described incidence of AKI that ranges widely from 0.5 to 36.6 % in COVID-19 patients [3].Early detection and precise treatments of AKI can implement better preventive strategies and prevent deterioration of renal function and renal failure, effectively contain progression of the COVID-19 hospitalized patients [4]. Among them, neutrophil gelatinase-associated lipocalin (NGAL) has been recognized as one of the promising biomarkers candidate for detection of AKI.…”
Section: Introductionmentioning
confidence: 99%